Influence of the contact model on the dynamic response of the human knee joint - Machado, Margarida F. (2011)
The goal of this work is to study the influence of the contact force model, contact geometry and contact material properties on the dynamic response of a human knee joint model. For this purpose a multibody knee model composed by two rigid bodies, the femur and the tibia, and four nonlinear spring elements that represent the main knee ligaments, is considered. The contact force models used were the Hertz, the Hunt-Crossley and the Lankarani-Nikravesh approaches. Results obtained from computational simulations show that Hertz law is less suitable to describe the dynamic response of the cartilage contact, because this pure elastic model does not account for the viscoelastic nature of the human articulations. Since knee can exhibit conformal and non-conformal contact scenarios, three different geometrical configurations for femur-tibia contact are considered, that is convex-convex spheres contact, convex-concave spheres contact and convex sphere-plane contact. The highest level of contact forces is obtained for the case of convex-convex spheres contact. As far as to the influence of the material contact properties is concerned, the dynamic response of a healthy and natural knee is analyzed and compared with three pathological and two artificial knee models. The obtained results demonstrate that the presence of the cartilage reduces significantly the knee contact forces.